2019
DOI: 10.1111/1365-2745.13260
|View full text |Cite
|
Sign up to set email alerts
|

Is phylogenetic and functional trait diversity a driver or a consequence of grassland community assembly?

Abstract: Community assembly changes fundamentally in response to disturbance following habitat destruction due to extreme events and human activities. There are several important aspects of community assembly that can be measured in response to disturbance or during species establishment. Of these measurable outcomes, metrics of taxonomic or species diversity (SD) are perhaps the most common and logistically the easiest to evaluate. It is increasingly evident that measurements of phylogenetic (PD) and functional trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
(74 reference statements)
1
25
0
Order By: Relevance
“…Inclusion of phylogenetic diversity in the response metrics in this study showed that aspects of community response to invasive species can control and drive ecosystem function in restorations [17,30]. Phylogenetic diversity can be a consequence of community assembly mechanisms in grassland restorations [31] and is not always congruent with patterns of taxonomic diversity [32]. Such insights from patterns of phylogenetic diversity into mechanisms can be relevant for assessing the impacts of invasive species [33].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of phylogenetic diversity in the response metrics in this study showed that aspects of community response to invasive species can control and drive ecosystem function in restorations [17,30]. Phylogenetic diversity can be a consequence of community assembly mechanisms in grassland restorations [31] and is not always congruent with patterns of taxonomic diversity [32]. Such insights from patterns of phylogenetic diversity into mechanisms can be relevant for assessing the impacts of invasive species [33].…”
Section: Discussionmentioning
confidence: 99%
“…To address these limitations, Graham and Fine (2008) first proposed phylogenetic beta diversity (PβD) as a measure of the evolutionary dissimilarity between communities, providing a more comprehensive framework to explain the role of historical imprints on community membership and how evolutionary legacy underlies patterns of niche divergence (Mouquet et al, 2012). Meanwhile, functional beta diversity (FβD), reflecting the morphological, ecological and physiological similarities between communities (Loiseau et al, 2017), was shown to better explain ecosystem functioning and species niche relationships than other classical measures of species diversity (García-Girón et al, 2019a;Jones et al, 2019). Recently, there have been several calls (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is now becoming clear that a simultaneous analysis of several diversity facets should provide the most basic building blocks to embrace the multifaceted nature of biodiversity and, at the same time, reveal aspects of community assembly beyond inferences that can be drawn from more traditional species-centred approaches (Jones et al, 2019). This reasoning is especially true from a conservation perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Such responses to anthropogenic nutrient enrichment have received relatively little attention (Yang et al, 2018;Yang et al, 2019). Phylogenetic diversity changes reflect the impacts of human disturbance activities on phylogenetic community structure and provide a mechanistic understanding of species coexistence within communities (Webb et al, 2002;Cavender-Bares et al, 2009;Jones et al, 2019). In general, two hypotheses are proposed to explain species loss under nutrient enrichment, i.e., the abundance-based and functional trait-based hypotheses (Suding et al, 2005;Yang et al, 2015).…”
Section: Nutrient Enrichment Impact On the Productivity-plant Divermentioning
confidence: 99%